2019
DOI: 10.1186/s42501-018-0018-y
|View full text |Cite
|
Sign up to set email alerts
|

The Jurassic fossil wood diversity from western Liaoning, NE China

Abstract: Western Liaoning is a unique region in China that bears diverse types of Jurassic plants, including leaves, fern rhizomes, and wood, providing significant proxy for vegetation and palaeoenvironment reconstruction of the well-known Yanliao Flora in East Asia. In particular, the silicified wood is very abundant in the fossil Lagerstätte of the Jurassic Tiaojishan Formation in Beipiao, western Liaoning. Previous and recent systematic investigations documented a high diversity of the Jurassic wood assemblages. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(4 citation statements)
references
References 32 publications
0
4
0
Order By: Relevance
“…Diverse and abundant permineralized plant remains are represented by fern rhizomes (Cheng & Li, 2007; Cheng, Wang, & Li, 2007; Tian et al, 2013, 2014,b; Zhang & Zheng, 1991), cycad stems (Zhang, Wang, Saiki, Li, & Zheng, 2006), as well as ginkgo and coniferous woods (e.g., Jiang et al, 2012; Jiang, Ferguson, Li, & Cheng, 2008; Tian et al, 2015; Wang, Saiki, Zhang, & Zheng, 2006), have been reported. In total, around 26 species across 17 genera of conifer wood have been described in this formation, although most of them are only preserved with secondary xylem (Jiang et al, 2019). Zhangoxylon is thus the first fossil wood taxa with anatomically preserved structures of pith, primary xylem, and secondary xylem.…”
Section: Resultsmentioning
confidence: 99%
“…Diverse and abundant permineralized plant remains are represented by fern rhizomes (Cheng & Li, 2007; Cheng, Wang, & Li, 2007; Tian et al, 2013, 2014,b; Zhang & Zheng, 1991), cycad stems (Zhang, Wang, Saiki, Li, & Zheng, 2006), as well as ginkgo and coniferous woods (e.g., Jiang et al, 2012; Jiang, Ferguson, Li, & Cheng, 2008; Tian et al, 2015; Wang, Saiki, Zhang, & Zheng, 2006), have been reported. In total, around 26 species across 17 genera of conifer wood have been described in this formation, although most of them are only preserved with secondary xylem (Jiang et al, 2019). Zhangoxylon is thus the first fossil wood taxa with anatomically preserved structures of pith, primary xylem, and secondary xylem.…”
Section: Resultsmentioning
confidence: 99%
“…Jiang et al reported that the Keteleeria liaoxiense and Keteleeria sp. were discovered from the Middle Jurassic Liaoning Province, but they did not give a description [ 36 ].…”
Section: Resultsmentioning
confidence: 99%
“…The systematic affiliation of Phoroxylon and Sahnioxylon is still unclear. In recent decades, some authors maintain that they belong to bennettitalean gymnosperms (Lemoigne & Torres 1988, Falcon-Lang & Cantrill 2001, Poole & Cantrill 2001; other authors think they represent an evolutionary transitional type and ancestral plant of angiosperms without vessels (see Jiang et al 2019). The studied fossil wood is homoxylous and pycnoxylic.…”
Section: Discussionmentioning
confidence: 98%